A Review on Explosive forming Process - Kumar, Sahil (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
This paper deals with study of explosive forming processes for making sphere of very thin metallic sheets Explosive Forming is a manufacturing technique that uses explosions to force the metal into dies and moulds. The explosives are either in direct contact with the materials or detonated underwater. This process is useful for short production runs of conventionally difficult-to-manufacture parts. Explosive forming is one of the non-traditional method, in which, most commonly, the water is used as the pressure transmission medium. In this paper, we are reviewing the researches done by various authors on explosive forming process for different materials.